Application of microwave in wood tomography - A. Jalil @ Zainuddin, Mohd. Hafiz (2005)
Wood degradation and defects, such as voids and knots, affect the quality of lumber. The ability to detect the internal defects in the log can save mills time and processing costs. In this case, the microwave propagation is used to investigate the internal defect of wood. The principle of this case study is to measure the attenuation of microwave signal when propagates through the wood. The microwave trainer Type (e) 4510 that transmit 14.5 GHz with 20mW microwave signal is used and the measurements are made in voltage using multi-meter that connected with detector. The development of amplification circuit has been developed to amplify the received signal from detector. Rubber wood is used as material under test, (MUT) with thickness used between 20mm to 60mm. The wood defection is created with known size and the wood is immersed in water in order to study the effect of moisture content on microwave signal. Several experiments must be performed with several samples of woods and results of measurement must be studied in order to determine the different measurement between the defect wood and good wood. Artificial Neural Network (ANN) is applied in Visual Basic to recognize the pattern voltage based on experiment data to develop 2D image and determine the internal characteristic of wood. All data presented are based on experiment results. The results from this work will determine the suitability to use microwave signal in wood scanning.